PEMANFAATAN BATU KAPUR DIDAERAH SAMPANG MADURA SEBAGAI BAHAN PENGGANTI AGREGAT KASAR PADA CAMPURAN BETON - Rochmah, Nurul (JHP17 (Jurnal Hasil Penelitian), 2016)
Concrete is important engineering material, expensive construction can be caused by increasing cost of concrete. In recent years, concrete production has increased which means consumption of coarse aggregate also increased. Natural coarse aggregate is gravel. Due to the growth in the construction industry, the demand for gravel is increasing rapidly, therefore gravel is expensive. Constructions companies which are close to Sampang are used to using limestone from Sampang as partial replacement of coarse aggregate for construction which are cheaper and greater available than gravel in order to reduce concrete cost. In this case there is a need to study the concrete with limestone from Sampang as coarse aggregate in order to get better understanding of limestone in concrete mixes. The aim of this research is to investigate the compressive strength of the concrete in which limestone from Sampang was used as coarse aggregate is partially or completely replaced.Â  The coarse aggregate was replaced withÂ  0%, 25%, 50%, 75% , 100% by limestone from Sampang, respectively. The compressive strengths of concrete speciemens for respective mix proportions were tested at 3, 7, 14 and 28 days of water curing. In addition the source aggregate properties were considered in this research : Los Angeles abrasion, absorption and spesific gravity for coarse aggregates and fine aggregate. The result of this investigation showed with the increase in the percentage of limestone from Sampang replacement in concrete, the compressive strength of the limestone from Sampang significantly increased.Keywords: concrete, coarse aggregate, limestone, compressive strength